2019
DOI: 10.31616/asj.2018.0209
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Rod Constructs Can Increase the Incidence of Iliac Screw Loosening after Surgery for Adult Spinal Deformity

Abstract: Study Design A retrospective study. Purpose To investigate the incidence of iliac screw loosening with a two-rod vs. multi-rod construct and the effect on clinical and radiographic outcomes after surgery for adult spinal deformity (ASD). Overview of Literature Multi-rod construct is useful for preventing rod fracture in ASD surgery. However, limited information is available regarding the incidence of iliac screw loosening after corrective fus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 31 publications
1
36
2
Order By: Relevance
“…Several papers have proposed methods to reduce RF. [18][19][20][21] Gupta et al 19 recommended the 4-rod technique for the PSO site. The point of maximum stress on the body is at its apex, where the spine becomes unstable by osteotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several papers have proposed methods to reduce RF. [18][19][20][21] Gupta et al 19 recommended the 4-rod technique for the PSO site. The point of maximum stress on the body is at its apex, where the spine becomes unstable by osteotomy.…”
Section: Discussionmentioning
confidence: 99%
“…This technique also helps to significantly reduce the potential for premature RF due to biomechanical damage of the rod. 20 Banno et al 18 reported that multirod structure use improved stability compared to use of the standard 2-rod structure, which was effective in preventing implant failure and symptomatic pseudarthrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Banno et al 24 compared multirod constructs versus standard 2-rod constructs in an elderly, osteopenic population undergoing ASD surgery. Patients with multirod constructs did have a higher incidence of iliac and UIV screw loosening, but a significantly lower incidence of rod fracture.…”
Section: Resultsmentioning
confidence: 99%
“…Combining lumbosacral and pelvic instrumentation with interbody cages represents an additional strategy to prevent mechanical complications [25,26]. Furthermore, Banno et al [27] investigated the incidence of proximal pedicle and iliac screw loosening with 2-rod versus 4-rod constructs. A radiologic halo developed around screws in 21% of patients with 2-rod versus 33% after 4-rod instrumentation.…”
Section: Discussionmentioning
confidence: 99%